UPAYA PENGEMBANGAN KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PENGGUNAAN MEDIA PEMBELAJARAN - Damis . (Idaarah: Jurnal Manajemen Pendidikan, 2017)
The problem of this paper is, how is the creativity of Islamic religious education teacher (PAI) in the use of instructional media and how the efforts of PAI teachers in the development of learning media and what constraints or obstacles faced by teachers of Islamic Education (PAI) in the development of creativity use learning media and How is the solution made by teachers of Islamic Education (PAI) in the development of creativity use of instructional media. Concluded that in learning Islamic Religious Education manually, in the learning process using learning media. Because in each class is prepared media LCD Prejector. But depending on the learning materials (conditional). In addition, teachers also have the creativity in using the existing learning media and use methods appropriate to the material that will convey, that is tailored to the material, objectives, methods, characteristics of students in the classroom, it is intended that the use of learning media does not deviate from materials, objectives, methods, characteristics of students so that students' understanding with the use of learning media can be more easily achieved.